2014
DOI: 10.1016/j.jeurceramsoc.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amount of doping agent on sintering, microstructure and optical properties of Zr- and La-doped alumina sintered by SPS

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Abstract SPS-produced ␣-alumina samples are prepared from powders doped with different amounts of Zr 4+ and La 3+ cations. Zr 4+ cations segregate at grain boundaries. m-ZrO 2 particles are formed at 570 but not at 280 cat ppm. A ␤-alumina LaAl 11 O 18 structure is found at 310 cat ppm when the lanthanum grain boundary solubility limit is exceeded (∼200 cat ppm). 100 cat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Doped powders (500 ppm (mole) of Mg and Y or 250 ppm Zr with respect to Al 2 O 3 ) were prepared by mixing 100 g of the alumina powder with respective amounts of suitable precursors: Mg(NO 3 ) 2 Á 6H 2 O (p.a., Lachema Brno, Czech Republic), zirconium acetate, and Y(NO 3 ) 3 Á 6H 2 O (99.8% purity, Sigma Aldrich). Zirconia was added in a lower amount than the other two dopants: formation of zirconia inclusions as a secondary phase was observed already at 500 ppm addition [25,38]. The presence of a second phase is undesirable in term of prospective application in preparation of fine-grained transparent alumina.…”
Section: Methodsmentioning
confidence: 99%
“…Doped powders (500 ppm (mole) of Mg and Y or 250 ppm Zr with respect to Al 2 O 3 ) were prepared by mixing 100 g of the alumina powder with respective amounts of suitable precursors: Mg(NO 3 ) 2 Á 6H 2 O (p.a., Lachema Brno, Czech Republic), zirconium acetate, and Y(NO 3 ) 3 Á 6H 2 O (99.8% purity, Sigma Aldrich). Zirconia was added in a lower amount than the other two dopants: formation of zirconia inclusions as a secondary phase was observed already at 500 ppm addition [25,38]. The presence of a second phase is undesirable in term of prospective application in preparation of fine-grained transparent alumina.…”
Section: Methodsmentioning
confidence: 99%
“…7a. It is well known that the second phase appears at grain boundaries and the triple points when its amount exceeds the grain boundary solubility limit [27]. The grain boundary solubility depends on both the grain size and the grain boundary phase orientation [28].…”
Section: Microstructurementioning
confidence: 99%
“…However, they also observed Cl in the secondary phase formed at the triple points of the La doped alumina grain boundaries in the EDX analysis of the samples in their later study. 11 Leipold and Kapadia 12 studied the effect of anion impurities (S 2− , Cl − , F − , OH − ) on hot-pressing of MgO. It was reported that the final density of MgO is reduced due to the presence of all the anion impurities in the temperature range of 850-1150 • C. The vapor pressure and second phase precipitate formation at the interfaces were proposed to be the contributing factors behind the effects of anion impurities.…”
Section: Introductionmentioning
confidence: 99%